New ASKAP radio supernova remnants and candidates in the Large Magellanic Cloud. Issue 2 (13th October 2022) - Bozzetto, Luke M; Filipović, Miroslav D; Sano, H; Alsaberi, R Z E; Barnes, L A; Bojičić, I S; Brose, R; Chomiuk, L; Crawford, E J; Dai, S; Ghavam, M; Haberl, F; et al.
ABSTRACT: We present a new Australian Square Kilometre Array Pathfinder (ASKAP) sample of 14 radio supernova remnants (SNR) candidates in the Large Magellanic Cloud (LMC). This new sample is a significant increase to the known number of older, larger, and low surface brightness LMC SNRs. We employ a multifrequency search for each object and found possible traces of optical and occasionally X-ray emission in several of these 14 SNR candidates. One of these 14 SNR candidates (MCSNR J0522 – 6543) has multifrequency properties that strongly indicate a bona fide SNR. We also investigate a sample of 20 previously suggested LMC SNR candidates and confirm the SNR nature of MCSNR J0506 – 6815. We detect lower surface brightness SNR candidates which were likely formed by a combination of shock waves and strong stellar winds from massive progenitors (and possibly surrounding OB stars). Some of our new SNR candidates are also found in lower density environments in which SNe type Ia explode inside a previously excavated interstellar medium.